DEVELOPING YOUTH CREATIVITY POTENTIAL IN MODERN SOCIETY - Nigora Yuldasheva (Bright Mind Publishing, 2025)
This article discusses the necessity and key factors for developing the creative potential of youth in the context of a rapidly evolving modern society. It also analyzes the role and significance of education, upbringing, social environment, and psychological approaches in fostering creativity in every young generation.
Keywords: Creative potential, innovative approach, non-traditional thinking, imagination, fantasy, cognition.